A Phenyl Thioether‐Based Probe: Zn2+ Ion Sensor, Structure Determination and Live Cell Imaging†. Issue 15 (17th April 2019) - Dey, Sunanda; Maity, Suvendu; Dasmahapatra, Ananya; Chattopadhyay, Debprasad; Sinha, Chittaranjan
Abstract: 3, 3′‐((1Z, 1′Z)‐(((Propane‐1, 3‐diylbis(sulfanediyl))bis(2, 1‐phenylene))bis(azanyyldiene))bis(methanylylidene))bis(2‐hydroxy‐5‐methylbenzaldehyde) (H2 ‐SAP), characterized by different spectroscopic data, exhibits yellow emission (λem, 560 nm) when binds with Zn 2+ in H2 O‐MeOH (1:9 v/v, HEPES buffer, pH 7.4) in a mixture of seventeen biologically important other metal ions. The limit of detection (LOD) is 9.0 nM which is far below the World Health Organization (WHO) recommended data. The composition of the complex, 1:1 Zn 2+ :SAP 2−, is supported by Job's plot, ESI‐MS and single crystal X‐Ray crystallographic structure. Intracellular Zn 2+ ion is detected in Vero Cells (African Green Monkey Kidney) by using the probe, H2 ‐SAP, in the cell lines under fluorescence microscope. The probe has successfully been applied to recover Zn 2+ in surface water. Abstract : A new Schiff base (H2 ‐SAP), exhibits yellow emission (λem, 560 nm) on binding with Zn 2+ in H2 O‐MeOH (1:9 v/v, HEPES buffer, pH 7.4) in presence of seventeen other metal ions with LOD, 9.0 nM. The 1:1 Zn 2+ :SAP 2− composition is supported by Job's plot, ESI‐MS and single crystal X‐Ray crystallographic measurement. Intracellular Zn 2+ ion is detected using H2 ‐SAP in Vero Cells (African Green Monkey Kidney) under fluorescence microscope. The probe has also successfully been applied to recover Zn 2+ in surface water.